Նահապետ Քուչակի կենսապատումը - Նարինե Կարախանյան (ՀՀ ԳԱԱ հրատ.)
В статье представлен роман Анны Петросян "Любовь обиделась на мир, она уходит" в контексте биографического жанра. Выясняется отношение писателя к вопросу интерпретации образа Кучака, рассматриваются композиционное развитие и некоторые художественные и стилистические особенности романа. This article is a review of Anna Petrosyan’s novel “Love Holding Grudge Against The World Goes Away” in the context of a biographical genre. Karakhanyan elucidates Petrosyan’s interpretation of Quchak’s character. The compositional development as well as certain artistic and stylistic features of the novel are also studied.
Keywords: Language and Literature